1999
DOI: 10.1159/000028061
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Signal-Transducing Molecules and Phenotypical Characteristics in Peripheral Blood Lymphocytes from Gastric Carcinoma Patients

Abstract: The mechanisms underlying the impaired immune response frequently observed in cancer patients are not fully understood. Alteration of T-cell-associated signal transduction molecules has recently been implicated in immune suppression in tumor-bearing hosts. Furthermore, T cells from tumor-bearing host, irrespective of the presence of the ζ-chain, showed a lack of proliferative activity and cytotoxic function. In the present study, we investigated the expression of the ζ-chain molecule and the p56lck Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Our finding that Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), by triggering oxygen radical formation in monocytes, induced the disappearance of CD3ζ from lymphocytes suggests that this peptide may contribute to lymphocyte dysfunction in gastric adenocarcinoma. It is noteworthy that changes typical for lymphocytes recovered from patients with invasive gastric carcinomas, such as CD3ζ downmodulation and apoptosis (23,39), were induced by the Hp(2-20) peptide in vitro. However, it should be emphasized that further studies are needed to clarify the putative role of Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), by triggering oxygen radical formation in monocytes, induced the disappearance of CD3ζ from lymphocytes suggests that this peptide may contribute to lymphocyte dysfunction in gastric adenocarcinoma. It is noteworthy that changes typical for lymphocytes recovered from patients with invasive gastric carcinomas, such as CD3ζ downmodulation and apoptosis (23,39), were induced by the Hp(2-20) peptide in vitro. However, it should be emphasized that further studies are needed to clarify the putative role of Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Release of DAMPs, which are especially targeted by TLR2 and TLR4 (140145) during cancer progression may cause chronic inflammation leading to down-regulation of the ζ chain of the T-cell and NK cell activating receptors [for comprehensive information on this topic see the review by Baniyash et al (146)], which entails T-cell and NK cell dysfunction, a phenomenon observed in some malignancies such as GC (147, 148), colon (149), prostate (150), cervical (151), and pancreatic cancer (152). In addition to immunosuppression, DAMPS appear to facilitate other processes during gastric carcinogenesis.…”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%
“…For example, colorectal cancer patients have abnormal plasma and erythrocyte fatty acid levels, as well as of their polyunsaturated metabolites (Robinson et al, 2001). Ultimately, in lymphocytes, because membrane physicochemical status and cell lipid metabolism play pivotal roles in signal transduction pathway(s) activities important in maintaining cell function (Kim et al, 1999), it would not be unexpected that disturbances in these parameters could result in altered immunocompetence in hosts with these affected cells. Fluorescence intensity of ABM in lymphocytes suspension tended to decrease with progression of cancer.…”
Section: Discussionmentioning
confidence: 99%